Penanaman Nilai Anti Korupsi Melalui Sikap Kerja Keras dalam Pembentukan Karakter Anak di SDN 023 Samarinda Utara - Eka Selvi Handayani; Euis Kusumarini; Mei Putri Anista; Tria Yesa Abdilla (Lembaga Pengembangan Kinerja Dosen, 2024)
Corruption remains a major challenge in Indonesia. Education plays a crucial role in instilling anti-corruption values from an early age to shape individuals with integrity. One of the core values in anti-corruption education is hard work, which contributes to developing children’s character, fostering independence, discipline, and perseverance. This study aims to analyze how instilling anti-corruption values through hard work can shape children's character in elementary schools. This socialization activities employs a direct socialization method involving students at SDN 023 Samarinda Utara through various activities, such as counseling, simulations, and educational games. The findings indicate that students experience an increased understanding of the importance of integrity and hard work in daily life. Participants demonstrated positive changes in attitude and behavior, such as increased motivation to complete school assignments honestly and responsibly. Thus, instilling anti-corruption values through hard work proves effective in shaping children’s character with integrity. Therefore, the continuation of anti-corruption education programs in schools is essential, involving teachers, parents, and the educational community to create a corruption-free generation.